Ethical role modeling as a leadership strategy for inclusive education development - Sulastri; Rambat Nur Sasongko; Muhammad Kristiawan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2026)
This study examines ethical role modeling of the school principal as a strategic driver in the development of inclusive education. Inclusive education requires not only structural readiness but also ethical leadership capable of fostering equitable learning environments; however, prior studies have predominantly emphasized pedagogical and infrastructural aspects rather than leadership exemplarity. This research aims to explore how ethical role modeling is enacted, experienced, and institutionalized in inclusive school practices. A qualitative phenomenological design was employed, conducted at a public junior secondary school implementing inclusive education. Participants were selected through purposive and snowball sampling, including the principal, teachers, administrative staff, and students. Data were collected through in-depth interviews, observations, and document analysis, and analyzed using qualitative descriptive procedures involving data reduction, categorization, and conclusion drawing. Findings reveal that ethical leadership is manifested through fairness, empathy, and moral responsibility, operationalized via behavioral consistency, disciplinary modeling, and value-based communication. These practices institutionalize inclusive policies, strengthen pedagogical readiness, and improve resource facilitation, thereby impacting inclusive school culture, teacher professionalism, and student participation. The study concludes that ethical role modeling functions as a moral institutional bridge, transforming inclusive values into sustainable educational practice. Therefore, leadership development programs and inclusive education policies should prioritize ethical exemplarity as a foundational competency to ensure sustainable and culturally embedded inclusive school transformation.